Recent nanotheranostics applications for cancer therapy and diagnosis: A review - Fahimeh Aminolroayaei; Daryoush Shahbazi‐Gahrouei; Saghar Shahbazi‐Gahrouei; Naser Rasouli (IET Nanobiotechnology)
Abstract Nanotheranostics has attracted much attention due to its widespread application in molecular imaging and cancer therapy. Molecular imaging using nanoparticles has attracted special attention in the diagnosis of cancer at early stages. With the progress made in nanotheranostics, studying drug release, accumulation in the target tissue, biodistribution, and treatment effectiveness are other important factors. However, according to the studies conducted in this regard, each nanoparticle has some advantages and limitations that should be examined and then used in clinical applications. The main goal of this review is to explore the recent advancements in nanotheranostics for cancer therapy and diagnosis. Then, it is attempted to present recent studies on nanotheranostics used as a contrast agent in various imaging modalities and a platform for cancer therapy.